An integrative taxonomy on the locally endangered species of the Korean Scarabaeus (Coleoptera, Scarabaeidae) - Han, Taeman; Kim, Jin Ill; Yi, Dae-Am; Jeong, Jongchel; An, Seung Lak; Park, In Gyun; Park, Haechul (Zootaxa, 2016)
The ball-rolling dung beetles of the genus Scarabaeus are very ecologically important for the recycling of feces of large herbivores and the related nature management. There has been a significant decline, however, in the numbers of many species at the population and individual levels. S. typhon is currently thought to be the sole member of Scarabaeus distributed in Korea; however, that species underwent serious local extinctions in the 1970s. Before planning a full-scale species recovery, it is important to have an understanding of the exact species diversity and genetic structures of the focal species. We therefore attempted an integrative taxonomy focused on the Korean population of S. typhon and also on S. pius and S. sacer, which were once thought to be distributed in Korea, using both morphological and molecular approaches. The results of both approaches reveal the Korean species of Scarabaeus to be S. typhon and S. pius. In particular, our molecular results inferred from cytochrome c oxidase subunit I genetic analysis show that S. typhon should be considered a single species despite having various haplotypes throughout its wide geographical range from Europe to Korea. We identified two distinct lineages of S. pius (groups A and B) across a wide distributional range. We conclude that the Korean specimens of S. pius belong to group A and that S. pius is new to Korea under the current taxonomic treatment.